Association Between Blood Heavy Metal Exposure and Sleep Duration Among Korean Adults: Data From the Korea National Health and Nutrition Examination Survey, 2005–2017 - Jueun Lim; Miju Kim; Whanhee Lee (Journal of Sleep Medicine, 2026)
Objectives: We evaluated the associations between blood mercury (Hg), lead (Pb), and cadmium (Cd) concentrations and sleep duration among Korean adults and explored whether these associations differed across subgroups.Methods: This cross-sectional study included 17,831 adults aged ≥20 years from the Korea National Health and Nutrition Examination Survey (KNHANES 2005–2017). Sleep duration was assessed using self-reported data. Associations between blood heavy metal concentrations and sleep duration were examined using complex-sample multiple linear regression, accounting for the survey design with adjustments for sociodemographic and health-related covariates.Results: In the covariate-adjusted models, higher blood concentrations of Hg, Pb, and Cd were significantly associated with shorter sleep duration. Sleep duration decreased by 0.113 hours per 10 μg/L increase in Hg (95% confidence interval [CI]: -0.183 to -0.043; p=0.002), 0.076 hours per 1 μg/dL increase in Pb (95% CI: -0.098 to -0.054; p